The Influence of Green Supply Chain Management Practices on Customers and Suppliers on Product Quality and Production Costs - Akbar, Ali; Santosa, Wahyuningsih; Darasih, Ratna (Golden Ratio of Data in Summary, 2025)
This study aims to examine the effect of Green Supply Chain Management (MRPH) practices on product quality and production costs. As the concern for environmental sustainability increases, MRPH has become an important element in managing an effective and efficient supply chain. This study evaluates how the implementation of MRPH with customers and suppliers affects product cost and quality. This study found that MRPH provides significant benefits in reducing production costs and improving product quality through internal environmental management and green innovation. The results show that MRPH with suppliers contributes to operational flexibility and cost reduction, while MRPH with customers enhances positive product perception and company reputation. In addition to economic benefits, green practices in the supply chain also play an important role in minimizing environmental impacts, potentially increasing the company's competitiveness in an increasingly environmentally conscious market. This study provides insights on the importance of MRPH integration in their business strategy to achieve cost efficiency and long-term operational sustainability.